Perde konumunun ve zemin sınıfının betonarme yapılardaki hasar oranına etkisi - Sayın, Erkut; Yön, Burak; Calayır, Yusuf (Erciyes Üniversitesi, 2010)
Bu çalışmada zemin sınıfına bağlı olarak perde konumlarındaki değişimin betonarme yapılarda oluşturduğu hasara etkisi incelenmiştir. Bu amaçla, perde konumları farklı olan üç adet yedi katlı düzenli betonarme yapı tasarlanmıştır. Bu yapıların yönetmeliğimizdeki dört adet zemin sınıfına göre deprem analizleri yapılmıştır. Analizlerden elde edilen sonuçlar, Deprem Bölgelerinde Yapılacak Yapılar Hakkında Yönetmelik (DBYYHY–2007) ’de belirtilen doğrusal elastik hesap yöntemine göre değerlendirilmiştir. Değerlendirmede, yapıların zemin katında seçilen kolon ve kirişler için perde konumu ve zemin sınıfına bağlı olarak etki/kapasite oranları kullanılmıştır. Perde konumu ve zemin sınıfı değiştikçe seçilen elemanların etki/kapasite oranlarında önemli farklılıklar gözlenmiştir. Çözümlerde SAP2000 yapı analiz programı kullanılmıştır.

In this study, the effect of the variation of shear wall locations to the damage of reinforced concrete buildings is investigated depending on the local site class. For this purpose, three regular reinforced concrete buildings with seven stories which have different shear wall positions are designed. Earthquake analyses of these buildings are performed using mode superposition method for four local site classes in the 2007 Turkish Earthquake Code for Buildings. Results obtained from the analyses are evaluated using the linear elastic method specified at the same code. In the evaluation, the demand/capacity ratios, calculated depending on shear wall locations and local site classes, are used for the selected columns and beams at ground floors of the buildings. Significant differences are determined at the demand/capacity ratios of the selected members as shear wall positions and local site class change. SAP2000 structural analysis program are used at solutions
Effect to damage ratio at reinforced concrete structure of shear wall location and local site class